Development of Mathematics E-Module to Improve Students' Mathematical Problem Solving Skills in Problem Based Learning Models - Maghfiroh, Khikmatul; Dwijanto, Dwijanto; Cahyono, Adi Nur (Universitas Negeri Semarang, 2024)
E-modules are electronic teaching materials that are designed practically and systematically to help students learn independently. The purpose of this study is to determine the validity, and practicality of the mathematics e-module of System of Linear Equations in Three Variables material, as well as to determine the magnitude of the increase in students' mathematical problem solving abilities. This research was a research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques use observation, interviews, questionnaires, tests, and documentation. The instruments in this study are learning implementation observation sheet, expert validation questionnaires and student response, list of interview questions, mathematical problem solving ability test questions, as well as documentation of research activities. The results showed that 1) media expert validation of 3.87 with very valid criteria and material expert validation of 3.71 with very valid criteria; 2) student response questionnaire of 3.26 with very practical criteria; and 3) the occurrence of an increase in students' mathematical problem solving ability by 0.49 with moderate criteria.